Fabrication, characterisation and oxidation behaviour of Pt-based bond coats for high temperature applications - Qian, Lingyi (2017)
Over the years, platinum modified aluminide (PtAl) bond coats have been used in high temperature protection systems for commercial aircraft engines to protect turbine blades from high temperature oxidation and corrosion. In the process of operation, the oxidation and rumpling behaviours of the bond coats are the key factors in determining the lifetime of the thermal barrier coating. The latest development in aircraft engines has given rise to the need for bond coats with better oxidation and rumpling resistance at high temperature. This investigation aims to improve the oxidation and rumpling resistances of general PtAl bond coats by introducing ZrO2 nanoparticles, Ir and Pd additions: ZrO2 nanoparticles were incorporated into PtAl bond coats by co electrodeposition in an attempt to enhance their performance by exploiting the effect of reactive element (Hf, Zr, etc.) oxides. PtAl coatings with and without ZrO2 nanoparticles were deposited onto three commercially available Ni-based superalloys, namely, Mar-M-247, Mar-M-246 and Inconel 718. Thermal cycling oxidation tests were performed to evaluate the influence of ZrO2 addition and substrate composition. The addition of ZrO2 particles to PtAl coatings on Mar M 246 and Inconel 718 appeared to accelerate the growth of thermally grown oxide and reduced the rumpling of thermally grown oxide. However, when depositing PtAl coatings with ZrO2 nanoparticles on Mar-M-247, there was no changes, as mentioned above, in thermally grown oxide. Through the analysis of the coatings on different substrates, the interactions among Hf, Al and ZrO2 have been revealed and clarified, which offers a better understanding of the reactions of ZrO2 and the influence of substrate composition on bond coats. Ir and Pd coatings were deposited by means of electroplating and electroless plating respectively to explore the effects of other platinum group metals. Ir-modified PtAl coatings were investigated on Mar-M-246 with different vacuum annealing durations before the cyclic thermal test, which presented a significant reduction in growth rate of TGO and inward diffusion of Al in the oxidation test. Instead of oxygen diffusion barrier, Ir exhibited a diffusion barrier to Al possibly by forming a high temperature solid solution with Al, which has a higher melting point than general β-NiAl phase. As a result, it restrained the inward diffusion of Al and slowed down the outward diffusion of Al, thus improving the oxidation resistance. In addition, Ir concentration produced an effect on the diffusion barrier of Ir. When it is reduced lower than 15 wt.%, the barrier effect of Ir begins to degrade, which provides a better comprehension of the diffusion barrier effect of Ir. However, Pd-modified PtAl coating did not strengthen oxidation resistance, which may be caused by the phosphorus precipitates generated from the electroless plating process. ZrO2 and Pd-modified PtAl bond coats were further investigated with 8 wt.% yttria stabilised zirconia top coat. Comparison between conventional PtAl and high velocity oxygen fuel sprayed NiCoCrAlY bond coats was made as well. Isothermal and cyclic thermal oxidation tests were carried out to evaluate the prepared bond coats. ZrO2 modified PtAl coating showed the best oxidation and rumpling resistance in cyclic thermal oxidation, while Pd-modified PtAl coating was worse than conventional PtAl coating and better than the NiCoCrAlY coating. It has been observed that ZrO2- and Pd-modified PtAl bond coats are affected by different methods of oxidation test. Isothermal oxidation has a greater impact on ZrO2- and Pd-modified PtAl bond coats. The difference is considered to be a consequence of long term annealing in isothermal oxidation, which leads to a fast grain boundary diffusion of Al.